The Effect of family, friends, and others on stress among Vietnamese university students: a survey study - Hoang, Hoc Trung; Nguyen, Thi Thuy Dung; Van, Hieu Hoang (International Journal of Innovative Research and Scientific Studies, 2025)
Social support is an important factor for people to cope with difficult situations. A cross-sectional study, 492 Vietnamese students who were selected using convenient sampling from September 2024 to December 2024. The data were collected using the Multidimensional Scale of Perceived Social Support (MSPSS) and Perceived Stress Scale (PSS). The collected data was analyzed using structural equation modeling (SEM) in AMOS 26. Structural equation modeling indicated a significant relationship between Other and stress (β=-0.012, SE = 0.019, p= 0.505), Family and stress (β = -0.032, SE = 0.017, p= 0.055), and Friend and stress (β = -0.097, SE = 0.022, p < 0.01). The results indicated that increasing social support could decrease stress. These results have important implications for higher education in promoting university students in Vietnam.